Pengembangan Sistem Informasi Manajemen Kepegawaian (Studi Kasus: RSUD Dr. Iskak Tulungagung) - Cindy Rizki Amalya; Adam Hendra Brata; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Current technological developments support the process of disseminating information quickly so that it can be accessed anywhere and anytime mobile. Not only government institutions or organizations based on information technology can enjoy the development of this technology. Other institutions and organizations also need to develop this technology to maximize the goals of the institution or organization. Likewise for RSUD Dr. Iskak Tulungagung, in order to provide maximum health services, surely there are a lot of employees needed. Therefore, there is a need for adequate employee management. But in its application, employee management is still done by storing employee data in the form of printed documents stored in a cupboard. So that there are still often problems such as the length of time in the search for data, storage of data that has not been arranged properly, and late notification to employees such as the existence of data that must be updated by employees. To handle with these problems, an Employment Management Information System (SIMPEG) was established which is expected to be able to solve these problems. This system is web based for easy access anytime and from anywhere through any device that has a browser and internet. In its development, using prototyping models to maximize the creation of a system in accordance with the wishes of the user. And to find out user satisfaction, a usability testing process will be carried out using the System Usability Scale (SUS) as the benchmark.